Three Dimensional Boundary Layer Flow of MHD Maxwell Nanofluid over a Non-Linearly Stretching Sheet with Nonlinear Thermal Radiation - B.J., Gireesha; Prasannakumara, B.C.; Umeshaiah, M.; N.S., Shashikumar (Journal of Applied Nonlinear Dynamics, 2026)
This research article investigates the magnetohydrodynamic (MHD) three-dimensional flow of Maxwell nanofluid by considering convective surface boundary condition. Flow is generated because of a nonlinear stretching from the surface in lateral directions. Temperature and nanoparticles concentration distributions are studied via the Brownian movement and thermophoresis results. The governing partial differential equations are converted to the system of nonlinear ordinary differential equations through the use of suitable transformations then the obtained equations are solved numerically by applying RKF-45 method. The convergence of its solutions to the various existing parameters is verified through graphs sketched for temperature, velocity and nanoparticles concentration distributions.